Can face recognition be selectively preserved in some cases of amnesia? A cautionary tale - JAMES WINGROVE (Cortex, 2024)
Evidence suggests that some patients with isolated hippocampal damage appear to present with selective preservation of unfamiliar face recognition relative to other kinds of visual test stimuli (e.g., words). Bird and Burgess (2008) formulated a review and secondary analysis of a group of 10 cases all tested on a clinical assessment of word and face recognition memory (RMT, Warrington, 1984), which confirmed the key memory dissociation at the group level. The current work provides an updated secondary analysis of such cases with a larger published sample (N = 52). In addition to group-level analyses, we also re-evaluate evidence using a single case statistical approach (Crawford & Garthwaite, 2005), enabling us to determine how many would make criteria for a ‘classical dissociation’ (Crawford, Garthwaite, & Gray, 2003). Overall, group-level analyses indicated the key pattern of significant differences confined to words was limited to small control sample comparisons. When using the large control sample provided by Bird and Burgess (2008), hippocampal cases as a group were significantly poorer for both classes of items. Furthermore, our single-case approach indicated few had a performance pattern of a relative difference across face > word categories that would meet statistical significance; namely within individual differences across categories that would warrant a significant ‘classical dissociation’. Moreover, these analyses also found several cases with a ‘classical dissociation’ in the reverse direction: namely preserved recognition of words. Such analyses serve to demonstrate the need for a more conservative statistical approach to be undertaken when reporting selective ‘preservation’ of a category in recognition memory. Whilst material specificity has important implications for understanding the role of the hippocampus in memory, our results highlight the need for statistical methods to be unquestionably rigorous before any claims are made. Lastly, we highlight other methodological issues critical to group analyses and make suggestions for future work.